Felix takes the stage - Lasky, Kathryn; Gilpin, Stephen (New York : Scholastic, 2010)
Having been discovered, a family of poisonous but friendly brown recluse spiders must flee their cozy home in a symphony hall and go searching for a new place to live.
Publisher's Weekly, May 2010
Booklist, May 2010
Horn Book, October 2010
Kirkus Review, April 2010
Library Media Connection, October 2010
4.7
Keywords: Brown recluse spider -- Juvenile fiction; Spiders -- Juvenile fiction; Home -- Juvenile fiction; Brown recluse spider -- Fiction; Spiders -- Fiction; Home -- Fiction; Brown recluse spiders -- Fiction; Spiders -- Fiction; Home -- Fiction